Digital Libraries and Recent Medical Informatics Research - Ammenwerth, E.; Knaup, P.; Maier, C.; Mludek, V.; Singer, R.; Skonetzki, S.; Wolff, A. C.; Haux, R.; Kulikowski, C. (Methods of Information in Medicine, 2001)
The Yearbook of Medical Informatics is published annually by the International Medical Informatics Association (IMIA) and contains a selection of recent excellent papers on medical informatics research (http://www.med.uni-heidelberg.de/mi/yearbook/index.htm). The special topic of the just published Yearbook 2001 is “Digital Libraries and Medicine”. Digital libraries have changed dramatically and will continue to change the way we work with medical knowledge. The selected papers present recent research and new results on digital libraries. As usual, the Yearbook 2001 also contains a variety of papers on other subjects relevant to medical informatics, such as Electronic Patient Records, Health Information Systems, Health and Clinical Management, Decision Support Systems, Education, as well as Image and Signal Processing. This paper will briefly introduce the contributions covering digital libraries and will show how medical informatics research contributes to this important topic.
Keywords: Medical Informatics; International Medical Informatics Association; IMIA; Digital Library; Yearbook